2017
DOI: 10.1002/advs.201600522
|View full text |Cite
|
Sign up to set email alerts
|

Label‐Free and Regenerative Electrochemical Microfluidic Biosensors for Continual Monitoring of Cell Secretomes

Abstract: Development of an efficient sensing platform capable of continual monitoring of biomarkers is needed to assess the functionality of the in vitro organoids and to evaluate their biological responses toward pharmaceutical compounds or chemical species over extended periods of time. Here, a novel label‐free microfluidic electrochemical (EC) biosensor with a unique built‐in on‐chip regeneration capability for continual measurement of cell‐secreted soluble biomarkers from an organoid culture in a fully automated ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
114
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(114 citation statements)
references
References 65 publications
0
114
0
Order By: Relevance
“…The microdevices with cell‐laden GelMA hydrogels were cultured in an incubator at 37 °C and 5% CO 2 . Using a WAGO controller and a customized MATLAB program to control solenoid valves, N 2 gas was propelled into the pressure chamber via the gas inlet . Cyclic compressions of 1 Hz were applied to the crosslinked hydrogel within the microdevices for 7 days of culture.…”
Section: Methodsmentioning
confidence: 99%
“…The microdevices with cell‐laden GelMA hydrogels were cultured in an incubator at 37 °C and 5% CO 2 . Using a WAGO controller and a customized MATLAB program to control solenoid valves, N 2 gas was propelled into the pressure chamber via the gas inlet . Cyclic compressions of 1 Hz were applied to the crosslinked hydrogel within the microdevices for 7 days of culture.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, microfluidics‐based electrochemical biosensors have been favored by researchers. Many microfluidics‐based electrochemical sensors have successfully demonstrated that they have great potential for biomarker detection . These detection chips for various antibody proteins have great potential for detection of exosomes.…”
Section: Detection Techniques For Exosomesmentioning
confidence: 99%
“…Indeed, a new trend in the field of organson-chips and in vitro tissue models is to harness the potential offered by the integration of sensing units with the culture chambers to continuously monitor the system. [17][18][19] The present work falls in this area as we have developed a strategy for a sensing device for stem cell differentiation monitoring, with the potential to be integrated within a cell culture chamber. Our technology is based on the coupling of the electrochemical properties of poly (3,4ethylenedioxythiophene): polystyrene sulfonate (PEDOT:PSS), and the specificity brought by monoclonal antibodies targeting the analyte of choice.…”
Section: Introductionmentioning
confidence: 99%